Budidaya Jagung dengan Populasi Tinggi untuk Meningkatkan Produktivitas dan Efisiensi Lahan di Indonesia: Budidaya Jagung dengan Populasi Tinggi untuk Meningkatkan Produktivitas dan Efisiensi Lahan di Indonesia - Wang Zhiwu; Chen Kai; Qi Shijun; Lu Zengbin; Cheng Wen; Xiao Huanying; Zhao Suxian; Yunus Musa; Rahmansyah Dermawan; Karlina Syahruddin; Ding Zhaohua (Universitas Bangka Belitung, 2019)
This study aims to support technically the use of space by adjusting the spacing and the use of high yielding new CI01, CI02 and CI03 maize varieties jointly developed by corn researchers from China and Indonesia with appropriate cultivation techniques. This experiment was conducted in March 2018 in Kediri, East Java, Indonesia. Planting is carried out in beds using plastic mulch. Planting was designed with a high population using a distance of 14 cm between plants, 2 rows per bed, and zigzag planted to obtain 99,000 plants/ha population. With this method, high yields of 13.35 t / ha for CI01 varieties, 13.72 t / Ha for CI02 varieties, and 12.78 t / Ha for CI03 varieties were obtained. The downy mildew disease rate was the lowest 0.8% in the CI01 variety. Economically, the use of high yield pattern planting methods increases yields by more than 20% and increases economic profit by 15% of the cost of corn production.